Design and implementation of a dynamic symbolic execution tool for windows executables. Issue 12 (20th May 2013) - Chen, Ting; Zhang, Xiao‐song; Zhu, Cong; Ji, Xiao‐li; Guo, Shi‐ze; Wu, Yue
SUMMARY Dynamic symbolic execution, or DSE for short, has become a promising technique in software testing. However, the implementation details of DSE have not been described in depth in existing works. Although some open‐source DSE tools are available nowadays, to design and implement a specific DSE tool from scratch is necessary for some reasons. To this end, we implement a Smart Fuzzing Tool for Windows Native Executables, or SMAFE for short, which utilizes Pin and STP for instrumentation and constraint solving, respectively. Advantages of Pin and STP make SMAFE portable. The major contribution of this paper is our detailed description of the implementation of DSE, including symbolization of inputs, tracking of symbols, synchronization of overlapped symbols, environment modeling, and so on. A practical case study validates the effectiveness of SMAFE. Then, the experiments with two benchmark sets present that the code coverage is above 90% on average. Benefits from this paper are at least twofold: moderating learning curve for scholars and shortening the development circle for practitioners. Copyright © 2013 John Wiley & Sons, Ltd.